Influence of sport-practice-hours on burnout and coping in table tennis players - Higinio González-García; Guillaume Martinent (Universidad de Granada, 2019)
The aim of this research was to analyse burnout (estimated by emotional and physical exhaustion) and coping (as estimated by the need to seek support) in relation to the number of sport-practice-hours undertaken by table tennis players of various levels of success. A sample of 180 Spanish table tennis players (mean age = 33.87 years; SD = 16.64; 149 men and 31 women) voluntarily participated in the study and filled out a series of self-report questionnaires. The results revealed that there was a significant difference among table tennis players on emotional and physical exhaustion (p < 0.01) with players who practiced more than ten hours reporting higher levels of emotional and physical exhaustion.  There was a  significant difference in coping behaviour (p < 0.01)   with players who practiced more than 10 hours reporting the greatest need. Finally, players who played at a higher level (nationally or internationally) had a greater number of  hours of training. It is concluded that players and coaches should take account of the time spent in sport-practice should because it can increase burnout levels in table tennis players. Moreover, coping skills could be influenced by sport-practice-hours, but further research should clarify these outcomes.